Freedom and Necessity in Modern Trinitarian Theology - Tanner, Norman (Asian Horizons, 2018)
Brandon Gallaher, Freedom and Necessity in Modern Trinitarian Theology, Oxford (UK): Oxford University Press, 2016. ISBN: 978-019-874460. Pages: xx + 298.